Supervisory policy stimulus: Evidence from the euro area dividend recommendation - Ernest Dautovic; Leonardo Gambacorta; Alessio Reghezza (European Central Bank (ECB), 2023)
At the onset of the Covid-19 outbreak, central banks and supervisors introduced dividend restrictions as a new policy instrument aimed at supporting lending to the real economy and strengthening banks' capacity to absorb losses. In this paper we estimate the impact of the ECB's dividend recommendation on bank lending and risk-taking. To address identification issues, we rely on credit registry data and a direct measure that captures variation in compliance with the recommendation across banks in the euro area. The analysis disentangles the confounding effects stemming from the wide range of monetary and fiscal policies that supported credit during the Covid-19 downturn and investigates their interaction with the dividend recommendation. We find that dividend restrictions have been an effective policy in supporting financially constrained firms, adding capital space to banks, and limiting procyclical behaviour. The effects on lending are larger for small and medium enterprises and for firms operating in Covid-19 vulnerable sectors. At the same time, we do not find evidence of a significant increase in lending to riskier borrowers and "zombie" firms.
Keywords: E5; E51; G18; G21; 330; Dividend restrictions; Supervisory policy; Credit supply; European Central Bank; Covid-19